2011
DOI: 10.1165/rcmb.2010-0454oc
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Peroxidase Signals via Epidermal Growth Factor–2 to Induce Cell Proliferation

Abstract: Eosinophils exert many of their inflammatory effects in allergic disorders through the degranulation and release of intracellular mediators, including a set of cationic granule proteins that include eosinophil peroxidase. Studies suggest that eosinophils are involved in remodeling. In previous studies, we showed that eosinophil granule proteins activate mitogen-activated protein kinase signaling. In this study, we investigated the receptor mediating eosinophil peroxidase-induced signaling and downstream effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In our prior work, we and others have shown that at even higher concentrations than studied here, of up to 10 microgram/ml (1–3 log order lower than those that are toxic) the granule proteins MBP1 and EPO prevent cell necrosis and apoptosis [45] , [46] via different mechanisms, indicating that the concentrations we used in these experiments are not toxic to these cells. Indeed, both granule proteins induce quite separate intracellular signaling pathways with different cellular consequences [20] , [47] . However, there has been little insight into the specific cellular receptors for these granule proteins, and this investigation is the focus of this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior work, we and others have shown that at even higher concentrations than studied here, of up to 10 microgram/ml (1–3 log order lower than those that are toxic) the granule proteins MBP1 and EPO prevent cell necrosis and apoptosis [45] , [46] via different mechanisms, indicating that the concentrations we used in these experiments are not toxic to these cells. Indeed, both granule proteins induce quite separate intracellular signaling pathways with different cellular consequences [20] , [47] . However, there has been little insight into the specific cellular receptors for these granule proteins, and this investigation is the focus of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in our laboratory, carried out in the neuroblastoma cell line IMR32, showed that EPO induced phosphorylation of HER2 at the Y1248 autophosphorylation site, and this led to loss of the cyclin-dependent kinase p27 kip from the nucleus and upregulation of the cell proliferation marker Ki67 [20] . These data suggest that EPO may be a ligand for HER2.…”
Section: Introductionmentioning
confidence: 88%
“…Through a chemical reaction called Fenton's reaction, H 2 O 2 can readily react with iron to convert it from ferrous (Fe 21 ) to ferric (Fe 31 ) and generate hydroxyl radicals ($OH). Alternatively, H 2 O 2 can react with H 1 and Cl 2 to make hypochlorous acid (HOCl) in the presence of myeloperoxidase (7) or, in the case of eosinophils, eosinophil peroxidase (8,9), which is a powerful oxidizing agent capable of oxidizing proteins and cell membranes, leading to damage and inflammation in the airways. Chloride channel 3 (CLC3) has been shown to regulate the production of O 2…”
Section: •2mentioning
confidence: 99%
“…(2) Tumor infiltrating eosinophils are part of host immune responses that include abilities to polarize T-cell functions, modulate humoral responses, or even be immunosuppressive in character. For example, the presence of IDO-positive eosinophils, 112 release of eosinophil granule proteins, 113 and the presence of IL-5 114 have all been shown to be protumorigenic, whereas in other instances eosinophils are antitumorigenic. 115 Indeed, animal studies addressing the relative role of eosinophils have been confounding.…”
Section: Cancer and Tumor Biologymentioning
confidence: 99%